IMPROVEMENT OF THE VEGETABLE OIL PRODUCTION TECHNOLOGY BY DEODORIZATION PROCESS USING FLOATING PACKING (Web of Technology: Multidimensional Research Journal, 2025)
This article explores the process of deodorization of vegetable oils and methods for its improvement. In particular, the deodorization process using floating packing is examined. The effectiveness of this method, its energy efficiency, and its impact on quality indicators are analyzed.